Globalization, Maritime Trade, and Foreign Direct Investment: Impacts on Ocean-Based Economic Growth and Development - Siti Nur Avira; Nabila Nada Jinan Nazifah (Professorline, 2026)
The expansion of globalization, international maritime trade, and foreign direct investment (FDI) has significantly reshaped the structure of ocean-based economies worldwide. As coastal and maritime nations seek sustainable growth, the blue economy has emerged as a strategic framework integrating economic development with environmental stewardship. This paper critically examines how globalization, maritime trade, and FDI influence economic growth and development in ocean-based sectors, including fisheries, ports, shipping, marine tourism, aquaculture, and offshore energy. Drawing on literature review and policy analysis, the study highlights both opportunities and challenges associated with global integration. While increased trade and FDI can stimulate technological transfer, infrastructure development, employment creation, and market access, they also pose risks such as resource overexploitation, environmental degradation, unequal benefit distribution, and dependency on multinational corporations. The paper argues that sustainable maritime development requires balanced governance, inclusive policies, and strategic investment in human capital, technology, and local entrepreneurship. It concludes by offering policy recommendations to ensure that globalization and FDI contribute not only to economic growth but also to equitable and environmentally responsible ocean-based development.